Modern thermodynamics : from hear engines to dissipative structures - Kondepudi, Dilip K.; Prigogine, Ilya. (Chichester : John Wiley and Sons, 1998)
This book presents an introductory text which covers both the traditional aspects of thermodynamics as well as its more recent developments.
Keywords: Thermodynamics; Thermodynamics